The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.22159/ijpps.2019v11i2.30170
|View full text |Cite
|
Sign up to set email alerts
|

The Enhancement of Collagen Synthesis Process on Diabetic Wound by Merremia Mammosa (Lour.) Extract Fraction

Abstract: Objective: This research aimed to evaluate the effect of fractionation of Merremia mammosa Lour. (Mm (Lour.)) extract on diabetic wound healing by observing collagen synthesis process and to search the most potent fraction.Methods: Wistar rats were divided into five groups (n=5), i.e., K-(negative control), K+ (positive control), K1 (ethyl acetate fraction), K2 (water fraction), and K3 (n-hexane fraction). The Mm (Lour.) was extracted with ethanol 70%, then fractionated by using three solvents which have diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“… 26 The transition from the inflammatory phase to the proliferative phase was hampered. This was relevant to the our previous studies 11 , 12 , 13 of diabetic wound, which showed that wound healing in the negative control took longer than in the positive control and treatment groups, as assessed via several wound parameters. This was also similar with the result of Ackermann et al.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“… 26 The transition from the inflammatory phase to the proliferative phase was hampered. This was relevant to the our previous studies 11 , 12 , 13 of diabetic wound, which showed that wound healing in the negative control took longer than in the positive control and treatment groups, as assessed via several wound parameters. This was also similar with the result of Ackermann et al.…”
Section: Discussionsupporting
confidence: 74%
“…This result was consistent with our previous study on Mm(Lour) extract fractions. 11 , 12 , 13 Therefore, the findings in this study allowed the presumption that the gel formulation of Mm (Lour.) water fraction possibly restored the delayed process of diabetic wound healing.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations